Civil Servant Preferences to Health Insurance Schemes: A Mixed Methodology Approach - Akinremi, Amos Oluwasayo; Coker, Marcellina Oluwatomi; Dosunmu, Afolabi Oladimeji; Adeniregun, Adedapo Olugbenga; Edun, Folarin Opeyemi; Amusa, Abiodun Richard (Advances in Social Sciences Research Journal, 2022)
Health insurance is aimed at building a healthier and more equitable society as millions of citizens are being driven into abject poverty because they must fund health care services from their own pockets. The purpose of this study was therefore to determine civil servants’ preferences as regards social health insurance and factors associated with willingness to join the scheme, based on the expected utility theory. The study adopted a mixed methodology with distribution of questionnaires among civil servants (across the length and breadth of the state from both the state secretariats and selected local government area (LGA) secretariats) and in-depth interview with Permanent Secretaries of selected State MDAs (Ministry Department and Agencies). The mean age of the respondents was 40.2 years ± standard deviation of 8.2 years. The study indicated some of the predictors of willingness to join the scheme as high level of satisfaction with health care system and trust in the management of the scheme (that is, having little concerns about the scheme management).